Political Communication of the Head of Korleko Village in Enhancing Developmental Innovation: Critical Discourse Analysis of Teun a Van Dijk - Hopizal Wadi; Fahrurrazi Fahrurrazi (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2022)
Communication is one of the channels to convey information to the public. The village head as the highest government head in the village is guided to be able to interact well and provide welfare to the entire community. Development innovation will never run well without effective communication between village heads, community leaders and local villagers. This study uses the critical discourse method of Teun A Van Dijk who pays attention to dismantling the political communication discourse of the Korleko village head hidden behind the text. The results of this study also show that the discourse that is built is not very effective in the interaction between the village head and the local community for the political communication channel in the public space is less effective to the community. As for others, such as the creation of information boards and the disclosure of the Village Budget as a form of transparency and effective public communication, are not optimally (closed). As a result, people who do not fully trust the village government demand the use of technological media such as Facebook, WhatsApp, Instagram and even YouTube to display Village Budgets as a form of honesty and one of the principles mandated by the Constitution.